The Town and Schools of Bazaar - Cathy Hoy (Symphony in the Flint Hills, 2010)
Bazaar was named by Martha (Mary) Leonard, first wife of Dr. M.R. Leonard, in memory of a shoppe or bazaar she had owned in Pennsylvania.
Keywords: small town; pioneer; Bazaar; schools; one room; church; post office; heyday; boarding house; public school; Mary Walton Leonard; Chase County; grade school; library